A cross-continental comparison of fruit-and seed-feeding insects in the rainforests of Panama, Thailand and Papua New Guinea - Dahl, Chris Nazipa (Jihočeská univerzita, 2019)
The aim of this thesis is to investigate community assemblages of fruit and seed feeding insects across three distinct biogeographic ForestGEO plots of Baro Colorado in Panama, Khao Chong in Thailand and Wanang in Papua New Guinea. It studies fruit and seed syndromes from which insects were reared per plant species across this rain forest plots, and describe host specialization in fruit and seed feeding insects. More specially, to compare seed feeding insects and their rate of seed attack among different insect groups are consistent across rainforest sites. Further it use plant phylogeny to explore plant floristic diversity, and explain ecological role of seed insect specialization in regulating plant species dynamic in maintaining high plant diversity in tropical rainforest regions.
A cross-continental comparison of fruit-and seed-feeding insects in the rainforests of Panama, Thailand and Papua New Guinea